Evolution of the immune landscape during progression of pancreatic intraductal papillary mucinous neoplasms to invasive cancer - Roth, Susanne; Zamzow, Katharina Morgane; Gaida, Matthias; Heikenwälder, Mathias; Tjaden, Christin; Hinz, Ulf; Bose, Promita; Michalski, Christoph W.; Hackert, Thilo (EBioMedicine, 2020)
Intraductal papillary mucinous neoplasm; Pancreatic cancer; Premalignant lesion; Tumour immunology; Tumour microenvironment
Gesehen am 10.06.2020